Data Exchange for Process Engineering – Challenges and Opportunities. Issue 3 (9th January 2019) - Fillinger, Sandra; Esche, Erik; Tolksdorf, Gregor; Welscher, Wolfgang; Wozny, Günter; Repke, Jens‐Uwe
Abstract: The ideas and requirements for digitization in the process industry are manifold – the interoperability of the tools in use by engineers is an important prerequisite. The strong heterogeneity of existing data formats and standards as well as the variety of proprietary and company‐specific solutions confronts the process industry with huge challenges. This paper deals with the data exchange between process simulation, 2D CAD, and 3D CAD tools, provides an overview of existing standards and formats as well as initial experiences gained in a case study. Abstract : Interoperability of the applied tools is an important prerequisite for digitization in process industry. The heterogeneity of existing data formats and standards as well as the variety of proprietary and company‐specific solutions is challenging. Here, a prototypical data exchange format between P&ID CAD, process simulation, and 3D CAD tools is presented.